Impactos da regulamentação estatal na gestão organizacional: o caso de uma cooperativa médica Unimed no Estado de Minas Gerais - Fatima Ferreira Roquete (2002)
The present studys objective was to analyze the impact of Government regulations on the managing of a Unimed health care co-op in the State of Minas Gerais. Within the context of Government Reform in Brazil, with the approval of Law n. 9.656, in June 1998, the activities of the companies that run private health care plans and insurance (or the segment of supplementary health care) in the Country were regulated. For such a study, a systemic approach to organizational analysis was used, and it dealt with six perspectives, that is, strategic, structural, technological, human, cultural and political. A Unimed health care co-op was chosen to be analyzed. This option was justified, particularly, by the fact that this kind of company is present in most regions and states in Brazil, and it is an alternative to the organizations of the competitive market. The study that was held was exploratory-descriptiveanalytic, and the approach adopted was that of qualitative analysis. Results demonstrated that those interviewed are aware of the environmental forces within this new context, to which the co-op is exposed. They reported that the organization has responded relatively quickly to environmental changes, mainly because a new administration, with a professional outlook, had taken over running the co-op in April 1998. Therefore, regulation offered the chance for this health care co-op to radically change its management style, thus becoming a professional and modern company. Strategic planning was adopted as a management tool, organizational strategies were altered, a new structure was implemented, deep and sweeping innovations were introduced in the technological area, and human resources relations were also changed. A highly qualified managerial team was set up, thus making administrative rationality available to the Unimed health care unit studied, which implied in the building a new culture. The restructuring of this organization, made necessary by the demands brought about by the regulation of the industry, has made viable not only its adaptation to this new context but also its survival and even its growth.